A Comparison of Achalasia Quality of Life Index and Eckardt Scores in Assessing Severity of Achalasia Cardia and Prognosis at 3 Months - A Single-Center Prospective Observational Study - Sreekumaran, Rajeevan; Ramamoorthy, Murali; Annasamy, Chezhian; Immaneni, Shubha; K, Muthukumaran; Karunakaran, Premkumar; Selvi, Caroline; A., Aravind (International Journal of Innovative Research in Medical Science, 2022)
Background: Eckardt score and Achalasia quality of life score (ASQ) are two scoring systems used in achalasia. This study tries to compare these scores in assessing the severity of the disease before and 3 months after initiation of treatment. Methods: 40 patients newly diagnosed with achalasia cardia were included in this study. Eckardt score and ASQ scores were calculated at the time of presentation. Patients underwent either Laparoscopic Heller myotomy (LHM), Pneumatic dilatation (PD), or medical management with isosorbide dinitrate (ISDN) after diagnosis. Patients were followed up after 3 months and these scores were assessed again to compare their reductions in different interventions. Results: The majority of the patients in this study underwent LHM (62.5%) followed by PD (32.5%). The average ASQ scores before and after PD were 20 and 12.8 respectively. The average ASQ scores before and after LHM were 20 and 12 respectively. The average Eckardt scores before and after the procedure were 8 and 2 in the PD group whereas this was 8 and 1.92 in the LHM group. There was a significant reduction in both Eckardt score and ASQ score after 3 months from baseline values in both the LHM and the PD groups (p<0.001) but not in the ISDN group. All the patients categorized as treatment success by the Eckardt score were similarly categorized by the ASQ score also. The percentage reduction in Eckardt score was found to be statistically significant and this was more in the LHM and the PD groups than in the ISDN group (p= <0.001). Percentage reduction in ASQ score post-procedure was not a statistically significant entity in any of the groups. Conclusion: Both the Eckardt score and Achalasia quality of life score are equally effective in assessing treatment response in achalasia cardia. The percentage reduction in Eckardt score after the procedure was found to be statistically significant in LHM and PD groups and not in the ISDN group. There was no statistically significant percentage reduction in ASQ score in any of the procedural groups.